2013
DOI: 10.1007/s11999-013-3043-2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Doxycycline Treatment of Aneurysmal Bone Cysts With Low Recurrence Rate: A Preliminary Report

Abstract: Background Aneurysmal bone cyst (ABC) has a recurrence rate of between 12% and 71% without en bloc resection or amputation. There is no percutaneous ABC treatment drug regimen demonstrating consistent evidence of bone healing with recurrence of \ 12%. Doxycyline has properties that may make it appropriate for percutaneous treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 44 publications
2
98
0
4
Order By: Relevance
“…Doxycycline (10 mg/mL) was used as the chemical ablation agent and delivered as a protein foam (mixture of doxycycline and 25% albumin and agitated with air to create a stable protein foam delivery system). 39 Doxycycline foam was injected into the cystic locules and, when possible, into the solid elements of the ABC. Postprocedural pain was managed with either oral NSAIDs or oral narcotic analgesics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doxycycline (10 mg/mL) was used as the chemical ablation agent and delivered as a protein foam (mixture of doxycycline and 25% albumin and agitated with air to create a stable protein foam delivery system). 39 Doxycycline foam was injected into the cystic locules and, when possible, into the solid elements of the ABC. Postprocedural pain was managed with either oral NSAIDs or oral narcotic analgesics.…”
Section: Methodsmentioning
confidence: 99%
“…38 The authors previously have reported pathologic specimens from 3 ABC patients treated with doxycycline injection 1 to 2 weeks before surgical resection with histologic evidence of tumor necrosis. 39 Seventy-one patients have been treated for ABC in the authors' institution. The purpose of this study is to answer 5 questions regarding percutaneous treatment of juxtaphyseal ABC with doxycycline: (1) Is there reduction of lytic bony destruction and evidence of new bone healing?…”
mentioning
confidence: 99%
“…Isolated intracystic injection of demineralized bone powder, bone marrow, calcitonin, bone substitute or doxycycline have given contradictory results and sometimes require a large number of procedures [10,22,26,27].…”
Section: Treatmentmentioning
confidence: 99%
“…53 It has been reported that occasionally these lesions heal spontaneously or after a pathological fracture or biopsy alone. 54 The recurrence rate of ABCs, particularly associated with juxtaphyseal locations in skeletally immature patients, 55 and the potential of disturbance of growth when the lesion is near a physeal plate after traditional surgical treatments is high and ranges from 30.8% to 50% according to Marcove et al, 56 Cole 57 and Schreuder et al 58 This suggests mini invasive management of ABCs such as embolization or sclerotherapy. Embolization of the feeding vessels was initially a pre-operative procedure performed to reduce intraoperative bleeding.…”
Section: Osteoid Osteomamentioning
confidence: 99%
“…Beyond simple cytotoxicity, doxycycline is antiangiogenic, a potent inhibitor of matrix metallo proteinase (MMP), an inhibitor of osteoclastic activity, induces apoptosis in osteoclasts and promotes osteoblastic activity. 54,[72][73][74][75] The authors reported a lesion volume reduction in all patients treated with one minor complication (skin necrosis) and 5% recurrence. Percutaneous sclerotherapy is well-described and is now the primary treatment of ABC in many centres; since surgical treatment may be difficult at certain sites, has higher risk of complications and a 10-44% local recurrence rate.…”
Section: Osteoid Osteomamentioning
confidence: 99%